Changes in the implantation procedures of pacemakers during the COVID-19 pandemic in Germany. (19th May 2022) - Schwab, JO; Wiese, J; Hauser, T
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): BIOTRONIC Background: During the beginning of the first pandemic wave beginning in spring 2020 a lot of elective EP procedures were set on hold. After a few months, the hospitals were allowed to proceed with their planned operations. The current investigation analyzed the changes in the number of cardiac pacemakers (PM) implantations in whole Germany. Methods: We performed a data retrieval of the number of monthly first-time pacemaker implantations, i.e. single-, dual-chamber, or CRT-P, for the 2019 pre- and 2020 pandemic from the "Institut für das Entgeltsystem im Krankenhaus" (InEK) using OPS codes. This database provides data of all in-hospital procedures in Germany. Results: The course of the implantation rates (January to September) is highlighted in the two figures, where figure 1 demonstrates the single- and dual-chamber PM, and figure 2 the CRT-P implantations in 2019 (blue line) compared to 2020 (red line). It can be clearly seen, that for the single- and dual-chamber PM, a gap occurs between March and Mai in 2020. On the contrary, for the sicker patients, who are in the need for CRT-P, the lines do no cross, significantly. Moreover, the number of CRT-P first-time implantations increased during May to September 2020. Discussion: The present study highlights the course of first-time pacemaker implantations throughout the beginning of the COVID-19 pandemic in whole Germany. In contrast to single- and dual-chamber PM implantation rates, the number of CRT-P implantations remained stable during the first three months of the pandemic and then exceeded the rates from 2019. The progressive nature of heart failure resulting in the need for CRT may be one reason for not postponing the first-time implantation in the months March to May 2020.